The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1121/1.4919350
|View full text |Cite
|
Sign up to set email alerts
|

Changes in otoacoustic emissions during selective auditory and visual attention

Abstract: Previous studies have demonstrated that the otoacoustic emissions (OAEs) measured during behavioral tasks can have different magnitudes when subjects are attending selectively or not attending. The implication is that the cognitive and perceptual demands of a task can affect the first neural stage of auditory processing-the sensory receptors themselves. However, the directions of the reported attentional effects have been inconsistent, the magnitudes of the observed differences typically have been small, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 61 publications
5
42
2
Order By: Relevance
“…In addition, results of the present study also showed a significantly lower noise floor for condition 2 (active listening) compared to other conditions, comparable to the results established by several investigators [132223]. Lower noise floor could be attributed to the efferent activity associated with the attentional demands of the behavioural tasks [23]. Another possible reason for lower noise floor is that when attending to auditory stimuli, listener might attempt to control physiological noise by limiting motion and controlling breathing [11].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, results of the present study also showed a significantly lower noise floor for condition 2 (active listening) compared to other conditions, comparable to the results established by several investigators [132223]. Lower noise floor could be attributed to the efferent activity associated with the attentional demands of the behavioural tasks [23]. Another possible reason for lower noise floor is that when attending to auditory stimuli, listener might attempt to control physiological noise by limiting motion and controlling breathing [11].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Walsh et al (2014;2015) reported a large decrease (~3 dB) in ear-canal noise in all of 447 their subjects when the subject did a behavioral discrimination compared to during passive listening. 448…”
Section: Comparison With Previous Reports 441mentioning
confidence: 85%
“…During both 63 auditory and visual tasks there was a reduction in ear-canal noise (i.e. a reduction in the nSFOAE) 64 relative to when the subject was presented the same stimuli but did not do a task (Walsh et al, 2014a;65 2014b, 2015. For an auditory task, the reduction was similar in both the attended ear and the 66 opposite ear.…”
Section: Introduction 47mentioning
confidence: 94%
See 2 more Smart Citations